Frontispiece: "Shine & Click" Photo‐Induced Interfacial Unmasking of Strained Alkynes on Small Water‐Soluble Gold Nanoparticles. Issue 5 (23rd January 2017) - Luo, Wilson; Gobbo, Pierangelo; McNitt, Christopher D.; Sutton, Dewey A.; Popik, Vladimir V.; Workentin, Mark S.
Abstract : Gold Nanoparticles The functionalization of gold nanoparticle (AuNP) surfaces to manipulate their chemical interactions at the interface is crucial for applications in chemical biology and materials science. A cyclopropenone‐based photochemistry was developed on AuNPs to provide access to interfacial strained alkynes that undergo fast and clean interfacial strain‐promoted alkyne‐azide and alkyne‐nitrone cycloaddition (i‐SPAAC and i‐SPANC, respectively) with azides and nitrones, which serves as a simple and versatile way to tailor AuNP surface properties and functionality. For more information, see the Full Paper by V. V. Popik, M. S. Workentin et al. onpage 1052 ff.